Bhāratīẏa bhāskarye mithuna - Sanyal, Narayan (Beṅgala Pābaliśārsa, 1980)
Study of the paired male and female (mithuna) motif in Indian temple architecture; includes notes on the use of the motif in Greek and Egyptian art.